Preparation, in vitro screening and molecular modelling of symmetrical 4-tert-butylpyridinium cholinesterase inhibitors--analogues of SAD-128 - Musilek, Kamil; Roder, Jan; Komloova, Marketa; Holas, Ondrej; Hrabinova, Martina; Pohanka, Miroslav; Dohnal, Vlastimil; Opletalova, Veronika; Kuca, Kamil; Jung, Young-Sik (Bioorganic & medicinal chemistry letters, 2011)
Carbamate inhibitors (e.g., pyridostimine bromide) are used as a pre-exposure treatment for the prevention of organophosphorus poisoning. They work by blocking acetylcholinesterase's (AChE) native function and thus protect AChE against irreversible inhibition by organophosphorus compounds. However, carbamate inhibitors are known for many undesirable side-effects related to the carbamylation of AChE. In this Letter, 19 analogues of SAD-128 were prepared and evaluated as cholinesterase inhibitors. The screening results showed promising inhibitory ability of four compounds better to used standards (pralidoxime, obidoxime, BW284c51, ethopropazine, SAD-128). Four most promising compounds were selected for further molecular docking studies. The SAR was stated from obtained data. The former receptor studies were reported and discussed. The further in vivo studies were recommended in the view of OP pre-exposure treatment.
Keywords: Catalytic Domain; acetylcholinesterasa; Pyridinium Compounds; molekulární modely; vztahy mezi strukturou a aktivitou; Computer Simulation; Structure-Activity Relationship; počítačová simulace; Cholinesterase Inhibitors; Models, Molecular; Binding Sites; organofosfáty; pyridinové sloučeniny; vazebná místa; Acetylcholinesterase; cholinesterasové inhibitory; katalytická doména; Organophosphates